Transverse fatigue behaviour of steel-UHPC composite deck with large-size U-ribs. (1st February 2019) - Liu, Yiming; Zhang, Qinghua; Meng, Weina; Bao, Yi; Bu, Yizhi
Highlights: Full-scale steel-UHPC composite deck specimen is tested under cyclic loadings. Transverse fatigue behavior of steel-UHPC composite deck is evaluated. The fatigue failure mode of steel-UHPC composite deck is determined. Effects of damage in UHPC layer and studs are quantified using a damage index. Abstract: With increasing traffic volumes, fatigue of orthotropic steel decks (OSDs) has become a critical issue in recent years. In this study, an innovative composite deck composed of large-size U-ribs, a thin ultra-high-performance concrete (UHPC) layer and headed studs is proposed to enhance the fatigue properties of OSDs. Experimental and numerical approaches were combined to investigate the transverse fatigue behaviour of the proposed composite deck. A large-scale composite deck specimen was fabricated and tested under cyclic loading. The experimental results revealed the progressive failure process of the composite deck. The effects of damage accumulation in UHPC layer and headed studs on the mechanical behaviour of steel-UHPC composite deck were evaluated. The results indicated that the mechanical degradation in the composite deck system accelerated the damage accumulation in the fatigue-prone details of OSDs. It is necessary to consider the effects of mechanical degradation in fatigue resistance evaluation.